Governance of the IMF : Evaluation Update. (Independent Evaluation Office Reports; Independent Evaluation Office Reports, 2018)
In 2008, the IEO undertook an evaluation on the IMF governance and concluded that effectiveness had been the strongest aspect of IMF governance, while accountability and voice had been the weakest. Since then, IMF governance has been strengthened aided by quota and voice reforms to address misalignments in shares and chairs as well as numerous improvements in governance procedures and practices. The update finds that IMF governance has proven its effectiveness in supporting the Fund to fulfill its mandates, but concerns remain on voice and accountability. Challenges remain related to representation and voice, interaction between governance bodies, the selection process for management, and the role of the G20 in IMF governance. Addressing these challenges will take time and may be subject to difficult tradeoffs between governance objectives such as preserving effectiveness while ensuring appropriate representation.